2014
DOI: 10.1002/adhm.201400377
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonded Multilayer Films Based on Poly(2‐oxazoline)s and Tannic Acid

Abstract: In recent years, the layer-by-layer (LbL) assembly based on hydrogen bonding interactions is gaining popularity for the preparation of thin film coatings, especially for biomedical purposes, based on the use of neutral, non-toxic building blocks. The use of tannic acid (TA) as hydrogen bonding donor is especially interesting as it results in LbL films that are stable under physiological conditions. In this work, investigations on the LbL thin film preparation of TA with poly(2-oxazoline)s with varying hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Additionally, the lower critical solution temperature (LCST) of hydrophilic POx can be tailored over a broad temperature range by means of the molar mass and composition adjustment, which is frequently required by diverse applications areas . Recently, POx and TA were also used to construct various multilayers …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the lower critical solution temperature (LCST) of hydrophilic POx can be tailored over a broad temperature range by means of the molar mass and composition adjustment, which is frequently required by diverse applications areas . Recently, POx and TA were also used to construct various multilayers …”
Section: Introductionmentioning
confidence: 99%
“…De Geest and Hoogenboom and their co‐workers demonstrated the LbL deposition of poly( n ‐propyl oxazoline) and TA at temperatures below or above the LCST of poly( n ‐propyl oxazoline) and found that the growth mechanism differs depending on the assembly temperature . In another study, the same researchers presented a detailed investigation of the thermodynamics of the multilayer assembly of poly(2‐alkyl‐2‐oxazoline)s and TA . Caruso and co‐workers prepared low‐fouling LbL capsules using either linear or brush‐like poly(2‐oxazoline)s and poly(methacrylic acid) (PMA) .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It consists of a center glucose molecule with all five hydroxyl moieties esterified with two gallic acid (3,4,5-trihydroxybenzoic acid) molecules. The trihydroxylphenyl groups play an important role in binding a variety of substrates through chemical and physical interactions, [3][4][5][6][7][8][9][10][11][12][13] which are similar to the adhesion mechanism of 3,4-dihydroxyphenylalanine (DOPA)-enriched adhesive proteins of blue mussels. 14 TA can be deposited onto various organic and inorganic substrates because of its inherent affinity towards surfaces.…”
Section: Introductionmentioning
confidence: 99%